2017
DOI: 10.1186/s40643-017-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of enzyme/metal-organic framework composites with high stability in protein denaturing solvents

Abstract: ObjectivesEnzyme/metal-organic framework composites with high stability in protein denaturing solvents were reported in this study.ResultsEncapsulation of enzyme in metal-organic frameworks (MOFs) via co-precipitation process was realized, and the generality of the synthesis was validated by using cytochrome c, horseradish peroxidase, and Candida antarctica lipase B as model enzymes. The stability of encapsulated enzyme was greatly increased after immobilization on MOFs. Remarkably, when exposed to protein den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 40 publications
5
89
0
Order By: Relevance
“…Researchers have successfully achieved a higher catalytic activity with a better recyclability while immobilizing laccase onto a bimodal micro‐mesoporous Zr‐metal organic framework . Also, a similar report suggested immobilization of lipase, HRP (horseradish peroxidase), and catalase into ZIF‐10, ZIF‐8, and ZIF‐90, respectively . Further, researchers also have immobilized multiple enzymes within a ZIF‐8 composite .…”
Section: Introductionmentioning
confidence: 97%
“…Researchers have successfully achieved a higher catalytic activity with a better recyclability while immobilizing laccase onto a bimodal micro‐mesoporous Zr‐metal organic framework . Also, a similar report suggested immobilization of lipase, HRP (horseradish peroxidase), and catalase into ZIF‐10, ZIF‐8, and ZIF‐90, respectively . Further, researchers also have immobilized multiple enzymes within a ZIF‐8 composite .…”
Section: Introductionmentioning
confidence: 97%
“…Zeolitic imidazolate framework (ZIF) materials belong to an important class of MOF (Phan et al 2010), which exhibit the tunable pore size, chemical functionality of classical MOFs, exceptional chemical stability, and structural diversity of zeolites (Wu et al 2007). Because of these features, ZIFs show great promise for enzyme immobilization (Hou et al 2017;Wu et al 2017). Hou et al (2015) reported the construction of mimetic multi-enzyme systems by embedding GOx in ZIF-8 and application of this system as biosensors for glucose detection, exhibiting extraordinary electro-detection performance, and lower detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve continuous synthesis in a PBR for the production of UDCA, we first tried to immobilize the four desired enzymes for use in cascade reactions (Scheme ). Initially, a number of immobilization carriers or methods were tested, including gel entrapment, cross‐linking with glutaraldehyde, metal–organic frameworks (MOFs), and inorganic crystal nanoflowers; however, the activities of the resulting immobilized enzymes were very low (data not shown). Finally, we chose commercially available resins with active epoxy groups as a carrier to immobilize the enzymes.…”
Section: Resultsmentioning
confidence: 70%